Nanotechnology for dryland agriculture water saving: Biodegradable hydrogel application in sweet corn (Zea mays saccharate Sturt) productio - Radian, Radian; Ichwan, Budiyati; Hayat, Islah; Hayat, Islah (Emirates Journal of Food and Agriculture, 2022)
This work aimed to determine the effect of biodegradable superabsorbent hydrogel based on cellulose derivatives on the growth and yield of sweet corn (Zea mays saccharata Sturt) on dry land. The design used was a completely randomized design (CRD). The applied treatments consisted of four levels of hydrogel: without hydrogel (control), 2, 4, and 6 g per plant, respectively. Each treatment was repeated six times in this experiment, yielding a total of 24 experimental pots. Each experiment pot contained 3 plants, thus all 72 plants. The results showed that the hydrogel would significantly increase soil moisture, relative water content, growth of the plant height, stem diameter, and ear cobs without corn husk. Likewise, on the length of the ear without ear cobs and wet ear weights without corn husk. As the hydrogel preserves soil moisture, allowing water to be available for the plant, it might also temporarily store soil from the water and gradually remove it into the soil. Further investigations should be performed to completely characterize the interaction between the superabsorbent hydrogel and the dry land soil.